Effects of climate change on vaccine storage and cold chain logistics: a qualitative study in Ogun State, Nigeria - Damilola Jeremiah Ayowole; Glory Olalekan Adebajo; Toheeb Omobolaji Lasisi; Jinod Gbolahan Bakai (BMJ Global Health)
Introduction Climate change remains a global challenge posing a significant risk to the vaccine cold chain system logistics. It threatens vaccine potency due to inadequate storage facilities and ineffective vaccine distribution mechanisms, which are mostly affected by unpredictable environmental conditions. In Nigeria, this situation is worsened by unreliable electric power supply, frequently interrupted alternative power sources, poorly trained cold chain personnel, and inefficient management procedures. These factors contribute to low immunisation coverage rates and high disease burdens. Hence, there is a need to assess the effect of climate change on cold chain system logistics.Method Participants were cold chain officers across vaccine cold stores in Ogun State, Southwestern Nigeria. Data were collected via a 35-item semistructured in-depth interview guide. The effect of climate change on vaccine storage and cold chain logistics efficiency in Ogun State, Nigeria, was assessed. Data were manually and thematically analysed using the constructivist variants of the grounded theory methodology. Ethical approval and participants’ informed consent were obtained.Result Participants perceived that increasing ambient temperature variability constrained cold chain performance, resulting in equipment deterioration or damage. The vaccine distribution mechanism is mostly interrupted by difficult transportation systems caused by unpredictable weather changes. Policies are required around prompt replacement of damaged resources, equipment, continuous training of skilled workers, monitoring and surveillance system improvement.Conclusion Climate change significantly affected the efficiency of the cold chain system. Relevant policy implementation was highlighted as an essential step towards alleviating its effects.